2018
DOI: 10.1155/2018/4153574
|View full text |Cite
|
Sign up to set email alerts
|

Serum 8‐Oxo‐dG as a Predictor of Sensitivity and Outcome of Radiotherapy and Chemotherapy of Upper Gastrointestinal Tumours

Abstract: The level of oxidative stress is important in the initiation and progression of various age-related diseases, such as cancer. The level of oxidative stress may also play a significant role in cancer patients' response to treatment. We aimed to investigate whether serum 8-oxo-dG as a marker of oxidative stress is a predictor of tumour response. We used modified ELISA with a two-step filtration to analyse 8-oxo-dG in serum. The relationship between 8-oxo-dG levels, tumour response, and toxicity was studied in 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…8A and B). Other researchers have demonstrated that ROS directly induced DNA oxidative damage [[27], [28], [29]], and we also found using immunofluorescence that 8-OHdG had the same trend as mitochondrial ROS (Fig. 8A and C).…”
Section: Resultssupporting
confidence: 81%
“…8A and B). Other researchers have demonstrated that ROS directly induced DNA oxidative damage [[27], [28], [29]], and we also found using immunofluorescence that 8-OHdG had the same trend as mitochondrial ROS (Fig. 8A and C).…”
Section: Resultssupporting
confidence: 81%
“…For the aromatic compounds (DNA/RNA), OH • can be added directly to produce hydroxylated radical adducts. These stable adducts such as 8-Oxo-deoxyguanosine [41,42] can be detected at extremely low concentration and used as a biomarker of OH • . When reacting with anions, OH • takes an electron, producing a corresponding new radical.…”
Section: Chemical Features Of Major Ros (Table 1)mentioning
confidence: 99%
“…One of the most frequently studied markers of oxidative DNA damage is the production of 8-oxo-dG, when ROS reacts with guanine bases in DNA ( 71 ). Several studies have shown that oxidative stress levels, based on 8-oxo-dG levels in urine or blood serum, may be a useful biomarker for determining the response to radiotherapy and chemotherapy in cancer patients ( 33 ). In most cases, chemotherapy accompanied by ROS overproduction results in elevated levels of 8-oxo-dG in patients with various types of cancer ( 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of 8-oxo-dG in tumors, blood samples or urine have been found in patients with various types of cancer ( 30 , 31 ). Moreover, 8-oxo-dG may be useful for predicting prognosis in different types of cancer ( 32 , 33 ). ROS levels are maintained within narrow limits under physiological conditions by an antioxidant defense system consisting of multiple independent components ( 34 ).…”
Section: Introductionmentioning
confidence: 99%